Decoding Komunikasi Nonverbal Pada Siaran Tv Kompas Malam (Riset Khalayak Pada Teman Tuli) - Nindia, Bunga Shafira; Susanto, Eko Harry; Salman, Doddy (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2020)
Abstract— Researchers want to find out how people with disabilities understand the content of news on television broadcasts, specifically decoding nonverbal communication on news broadcasts. Basically the communication process (message exchange) will not run well if it is not supported by various communication elements or components, namely encoding. Therefore, in communicating there are so many obstacles and constraints experienced by communication agents. Physical barriers become one of the obstacles in communication. When communicating, one's physical imperfections become a problem in the delivery and reception of messages (information). In this study, researchers used qualitative research methods and interpretive paradigms to get accurate results. After conducting research on persons with hearing impairments, the researcher saw that the resource persons could not encode or decode perfectly, the resource persons were only able to absorb a little information that was conveyed. The resource person is not able to make messages according to a certain code the cause is the unclear tempo of the sign language column movement that is too fast so the resource person is unable to capture the message conveyed by the interpreter. Keywords—: News; Communication; Encoding; Decoding; Deaf.